Chemical state and atomic scale environment of nickel in the corrosion layer of irradiated Zircaloy-2 at a burn-up around 45 MWd/kg. (October 2018) - Kuri, Goutam; Ramanantoanina, Harry; Bertsch, Johannes; Martin, Matthias; Panas, Itai
Highlights: Atomic-scale microstructural changes in the Ni-containing SPP and state of solute Ni present in the corrosion layer have been studied. Chemical state and Ni speciation in the oxide have been obtained by synchrotron X-rays experiments, and compared with DFT calculations. The Ni-bearing SPP in the oxide are neither fully dissolved nor entirely oxidized. Solute nickel in the oxide layer is present in a divalent state adjacent to oxygen vacancies. Role of Ni on the hydrogen ingress behavior in irradiated Zircaloy-2 is discussed. Abstract: Zircaloy-2 is used as fuel cladding in commercial boiling water reactors (BWR). A limiting factor for fuel longevity is the waterside corrosion of the cladding during in-service reactor operation and associated hydrogen pickup to the alloy. It is well known that the alloying elements (such as Cr, Fe, Ni etc.) including intermetallic precipitates (also termed as SPP) distribution influences both the oxidation process and hydrogen uptake evolution in this material. This paper reports an experimental investigation on the atomic scale microstructure of nickel-containing intermetallic particles with an emphasis on the oxidation and nickel-dissolution of SPP, and a combined experimental and computational study of solute nickel located in the corroded zirconium oxide microstructure. An irradiated cladding sample, taken from a BWR fuel rod, was prepared for the analysis using electron probe microanalysis (EPMA) and synchrotron-based micro-beam X-ray techniques (μXRF, μXRD and μXAS). The results show that the Ni-bearing SPP in the oxide layer are neither fully dissolved nor entirely oxidized at the given burn-up of the sample investigated. Conversely, all solute nickel present in the corroded layer is mostly oxidized and has an apparent homogeneous Ni 2+ distribution. By analyzing the μXAS spectra measured at the Ni absorption edge, we have obtained quantitative structural information about both irradiated SPP and the Ni coordination environment in the corrosion layer. There exists strong structural disorder in intermetallic Ni-bearing SPP as also evidenced by μXRD study. The basic structure away from SPP in the oxide area is composed of oxidized nickel atoms adjacent to oxygen vacancies. Finally, first-principles density functional theory (DFT) calculations have been used to discern the nickel speciation in zirconium oxide microstructure that is complementary to the multitude of experimental information. From this joint theoretical and experimental approach, significant insights into the structural specificity of Ni 2+ ions in monoclinic ZrO2, electronic factors governing the electron transport processes in the corrosion layer, and the apparent influence of nickel on the hydrogen ingress behavior in Zircaloy-2 are obtained.